The evaluation analysis of gender vocational students on traumatic experience in educational context - Firman, Firman; Hafina, Anne; Suwarjo, Suwarjo; Karneli, Yeni; Tririzky, Reza; Asri, Robbi; Syahri, Lia Mita (Institute of Advanced Engineering and Science, 2025)
Students, including vocational school students, are vulnerable to traumatic experiences (TE). Students still look normal but experience stress that interferes with learning activities. TE can be observed through positive psychological attributes such as self-love (SL), compassion, gratitude, and happiness. This study aimed to explore the gender-specific views of vocational school students regarding their TE to provide results that can be the basis for the implementation of gender-differentiated interventions in schools. A cross-sectional survey using quantitative methods was conducted and involved 498 vocational school students in West Sumatra, Indonesia. Data were collected using questionnaires with reliability from the range of 0.74-1 through reliability analysis and also analyzed in a multi-group setting through structural equation model (SEM) on SmartPLS 3 application. Importance-performance map analysis (IPMA) method was also used to assess the functionality of variables in the study. The results showed that positive psychological attributes interact, relate, and have a role in the TE of vocational students, including in the evaluation of gender analysis. The results of the study can be a reference to reduce the impact of TE for vocational students, especially by gender-specific vocational schools. For future research, TE can be studied with other positive psychological attribute variables over a longer period of time.